EFEKTIVITAS PENGGUNAAN FILE MANAGER PADA PEMBELAJARAN DINAMIKA PARTIKEL - Pranata Viki Karamoy; Djeli Alvi Tulandi; Patricia Mardiana Silangen (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
Education is a fundamental thing that must be considered in order to improve the quality of human resources. This study aims to determine the effectiveness of using the media file manager in learning particle dynamics. This research was conducted at the Physics Department of FMIPAK, Manado State University. The subjects in this study were taken using simple random sampling technique with second semester physics students as research subjects and in the design using one group pretest posttest. The instrument in this study was a test in the form of essay questions in the form of a pretest and posttest to measure students' cognitive learning outcomes after being given treatment. Based on the results of the study, it was calculated using the paired sample t-test from the results of the pretest posttest sig <0.05 and the N-gain test was 0.7 with a gain value of 70%. So through the above explanation it can be concluded that the hypothesis is accepted, meaning that the use of media file managers in particle dynamics learning is effective in improving student learning outcomes.